Comparative Statistical Assessment of Innovation Activity of the Industrial Sector of the Economy of Ukraine (Regional Context) - Ishchuk, S. O.; Sozanskyy, L. Yo. (Statistics of Ukraine, 2022)
Innovation largely determines the dynamics of gross value added, profit, productivity, and hence the level of wages. Accordingly, intensive innovation of industrial enterprises is one of the most important prerequisites for effective socio-economic development of the country. The aim of the article is to determine the trends of innovation activity of the industrial sector of the economy of the regions of Ukraine on the basis of comparative statistical evaluation. According to the results of the analysis, the share of innovative products in the volume of sold industrial products in Ukraine is the lowest among European countries, in particular in 2020 it was 1.9% (compared to 3.3% in 2013), while in Poland the value this figure was over 9%, and in Germany – 18%. The low level of innovation in industrial products in Ukraine is a direct consequence of the relatively low cost of innovation (0.47 billion euros in 2020 against 4.58 billion euros in Poland and 133.2 billion euros in Germany), the volume of which during 2012–2020 decreased by more than 70%. It is analytically proved that the innovation activity of the industrial sector of Ukraine’s economy in the regional context is extremely uneven. In particular, the undisputed leader (with a significant gap from other regions) in terms of sales of innovative products in the domestic and foreign markets, as well as in terms of spending on innovation was Donetsk region, while the largest number of innovative enterprises was Kharkiv region. It is revealed that in general the high export orientation of innovative products of domestic industry is provided by medium-low-tech industries (metallurgy; production of rubber and plastic products; repair and installation of machinery and equipment). In contrast, Ukraine has a high import dependence in the segments of intermediate and final consumption of high- and medium-high-tech products, including machine-building, textile, chemical and pharmaceutical. This indicates the existence of systemic problems related to the influence of a number of macroeconomic factors (especially the situation in certain markets) and a weak system of government incentives and regulation of innovation and protection of national economic interests.